Molecular characteristics of unknown chlorinated disinfection byproducts during chlorination in sedimentation sludge water. (1st July 2022) - Qian, Yunkun; Guo, Jun; Shi, Yijun; Chen, Yanan; Wang, Xinyi; Ma, Jiaxin; An, Dong
Abstract: Recycling sedimentation sludge water (SSW) supernatant to the head of drinking water treatment plants also recycles a large fraction of dissolved organic matter (DOM), which can react with chlorine to generate abundant DBPs. Among them, the majority of Cl-DBPs are not well understood. We characterized the DOM and chlorinated DBPs (Cl-DBPs) during the chlorination of SSW using Fourier transform ion cyclotron resonance mass spectrometry. Aromatic compounds and oxidized molecules preferentially reacted with chlorine to form aromatic DBPs. The unknown non-nitrogenous Cl-DBPs (i.e., CHOCl and CHOSCl) contained a large amount of aromatic ring structure, easily reacting with chlorine to form aromatic DBPs. During chlorination reaction, one precursor could be associated with 1–4 products, and one product can be associated with 1–7 precursors. The primary reaction was +Cl–H, +ClO–H, and +HClO, possessing the largest number of possible precursor-product pairs. Vascular plant-derived polyphenols, which are regarded as highly unsaturated and phenolic compounds were the primary precursors participated in the chlorination reaction. The products mainly distributed in the area with highly unsaturated and phenolic compounds illustrated that unknown Cl-DBPs had a large number of highly unsaturated bonds and aromatic rings showing the high toxicity. Understanding the transformation of DOM and characteristics of unknown Cl-DBPs may not only lead to development of more effective treatment strategies to minimize the formation of DBPs in recycled SSW but also can be extended to understanding unknown DBPs and their precursors in drinking water sources. Graphical abstract: Image 1 Highlights: Aromatic compounds and oxidized molecules were highly reactive with chlorine. Substitution reaction occupied the absolute predominance. Addition reaction mainly occurs in high aromatic compounds. Highly unsaturated and phenolic compounds were the primary DBP precursors. The products showed the high unsaturation and aromaticity.